Social Protection Of Rejang Lebong City Cleaning Officers in Improving Religious Attitude and Self Regulation - Eka Yanuarti; Agita Misriani; Reka Amelia Lestari; Fadila fadila (FOKUS Jurnal Kajian Keislaman dan Kemasyarakatan, 2023)
City cleaners, is one of the important calls that we often ignore and as if never ogle the general public. This call that is often misunderstood plays an important role in the pattern of the existence of a city. City cleaners work most of the day. The objectives of this study are 1) to increase social protection for city cleaning officers in Rejang Lebong Regency, 2) to increase religious attitudes and self-regulation for city cleaning officers in Rejang Lebong Regency. The research used the PAR (participatory action research) research method. The steps taken are planning, action, perception and reflection. Respondents in this study were 44 cleaners. The results of this study indicate that 1) The condition of the religiosity of the Rejang Lebong janitors with a total score of 4979. The condition of self-regulation of the cleaners in Rejang Lebong with a total score of 5684. 2) The social protection given to the janitors is giving religious lectures and counseling, providing assistance to cleaning staff, providing worship practice training, and providing training in improving the reading of the Qur'an. 3) The religiosity condition of the Rejang Lebong janitor increased by 12% from the total score of 4979 (44%) before the action to 6415 (56%) after the action was carried out. The condition of self-regulation of the cleaners in Rejang Lebong increased by 10% from the total score of 5684 (45%) before the action to 6999 (55%) after the action was carried out. providing worship practice training, and providing training in improving the reading of the Qur'an. 3) The religiosity condition of the Rejang Lebong janitor increased by 12% from the total score of 4979 (44%) before the action to 6415 (56%) after the action was carried out. The condition of self-regulation of the cleaners in Rejang Lebong increased by 10% from the total score of 5684 (45%) before the action to 6999 (55%) after the action was carried out. providing worship practice training, and providing training in improving the reading of the Qur'an. 3) The religiosity condition of the Rejang Lebong janitor increased by 12% from the total score of 4979 (44%) before the action to 6415 (56%) after the action was carried out. The condition of self-regulation of the cleaners in Rejang Lebong increased by 10% from the total score of 5684 (45%) before the action to 6999 (55%) after the action was carried out.